Endoscopic balloon dilatation versus endoscopic sphincterotomy for the removal of bile duct stones: a prospective randomised trial - Vlavianos, P (Copyright 2003 by Gut, 2003)
Background: Endoscopic balloon dilatation (EBD) of the sphincter of Oddi has been proposed as an alternative therapy with possible advantages, as compared with endoscopic sphincterotomy (ES), for removal of bile duct stones. Patients and methods: In a randomised study, we compared the efficacy and complication rate of the two techniques in 202 patients with common bile duct stones. Patients were followed up for 12 months. Results: A total of 103 patients were randomised to the EBD group and 99 to the ES group. Overall duct clearance was 87.1% and did not differ between the two groups (EBD 87.4%; ES 86.9%). The complication rate at 24 hours was 6.8% in the EBD group and 3.0% in the ES group (NS). Complications during follow up were 11.7% and 15.2% respectively (NS). A multivariate logistic regression analysis showed only the size of the largest stone to be predictive of success for either technique. Conclusion: Endoscopic balloon dilatation offers no significant advantage over the well established technique of endoscopic sphincterotomy for the removal of bile duct stones.